Promoting health: action in infant nutrition - doi: 10.4025/actascihealthsci.v35i1.14045 - Silveira, Vanessa Gomes; Gurgel, Adryana Aguiar; Albuquerque, Conceição Maria de; Frota, Mirna Albuquerque; Casimiro, Cintia Freitas; Oliveira, Isabely Costa Lima de (Acta Scientiarum. Health Sciences, 2012)
Thousands of children under five die from preventable diseases. Community interventions that emphasize primary care on health and nutrition have been identified as one of the solutions to overcome this problem. This study aimed to develop educational workshops to improve the perception of mothers about infant nutrition, using a qualitative approach with technical educational workshops, in a Health Unit of the City of Fortaleza, during the period from February to June 2008. The seven participants were mothers accompanying their children in childcare consultation. The analysis of data was made through a survey and saturation of responses, from where the thematic categories emerged: the contribution of educational workshops, breastfeeding and introduction of complementary feeding. The educational activities allowed a better awareness of mothers in relation to child nutrition and development of critical awareness of their essential role on children nutrition. In conclusion, the professional should emphasize the importance and benefits of adequate diet, and for this is necessary educational strategies in health, offering exchanges of knowledge, since they are different experiences in which the learning is significant.